2013
DOI: 10.1007/jhep05(2013)053
|View full text |Cite
|
Sign up to set email alerts
|

Consistent on shell renormalisation of electroweakinos in the complex MSSM: LHC and LC predictions

Abstract: Abstract:We extend the formalism developed in ref. [53] for the renormalisation of the chargino-neutralino sector to the most general case of the MSSM with complex parameters. We show that products of imaginary parts arising from MSSM parameters and from absorptive parts of loop integrals can already contribute to predictions for physical observables at the one-loop level, and demonstrate that the consistent treatment of such contributions gives rise to non-trivial structure, either in the field renormalisatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
71
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(73 citation statements)
references
References 170 publications
2
71
0
Order By: Relevance
“…In ref. [15,19], it was shown that in the CP violating case, the 1-loop corrections to the phases of M 1 and µ, i.e. φ M 1 and φ µ respectively 1 are UV finite.…”
Section: Nlo Contributions and Renormalizationmentioning
confidence: 99%
See 4 more Smart Citations
“…In ref. [15,19], it was shown that in the CP violating case, the 1-loop corrections to the phases of M 1 and µ, i.e. φ M 1 and φ µ respectively 1 are UV finite.…”
Section: Nlo Contributions and Renormalizationmentioning
confidence: 99%
“…[19], within the complex MSSM; examples for the contributing self-energy, vertex and box diagrams are shown in fig. 2.…”
Section: Nlo Contributions and Renormalizationmentioning
confidence: 99%
See 3 more Smart Citations